Microbiological characteristics of the soil after conversion of tropical forest and pasture into citrus grove - Nucci, Thais [UNESP]; Nahas, Ely [UNESP] (My University, 2013)
Citriculture is expanding into forests and pastures. Such changes in land use provide an opportunity to evaluate differences in soil microbiological and chemical characteristics related to C, N, and P cycles between tropical forest, pasture, and orange grove (Citrus sinensis L. Osbeck). The aim was to identify soil characteristics related to the conversion of a sustainable forest system into pasture and later into orange crop. Soil samples were collected from areas of forest, pasture, and both the top (T/ orange) and bottom (B/orange) of an orange grove. The numbers of bacteria and fungi, as well as potential nitrification, respiratory, ureolytic and phosphatase activities were determined. The lowest bacterial counts were found in the pasture soil and the highest in the forest soil. Fungi were significantly (p<0.05) more numerous in the orange grove soil than in the other soils. Respiratory activity in the forest and B/orange soils was lower than in the other soils. No difference was observed in the potential nitrification among the studied soils. Phosphatase and urease activities decreased in the following order: forest > pasture > B/orange > T/orange, although a significant difference was only found between the forest and T/orange soils. Significant differences in the organic matter content were found between the T/orange and the forest soils, and in the soil moisture between the T/orange and B/orange soils. In general, the microbiological and chemical characteristics found in the forest soil were less changed in the B/orange soil than in the T/orange and pasture soils. The characteristics studied related to the C, N, and P cycles were important to evaluate the impact of changes in soil quality.
Keywords: Citriculture; Potential nitrification; Respiratory activity; Soil enzymes; Soil quality